The role of food consumption value and attitude toward food on behavioral intention: Culinary tourist behavior in Indonesia - Sienny Thio; Monika Kristanti; Michael Ricky Sondak (Cogent Business & Management, 2024)
Eating local dishes at a destination is crucial for tourists. This study examines the key drivers of foreign tourists' behavioral intention toward local Indonesian food. A model examining food consumption value, attitude toward food, and behavioral intention was investigated using partial least squares structural equation modeling (PLS-SEM). A five-point Likert questionnaire was distributed to 468 international tourists visiting Bali and Java Island in Indonesia. The empirical findings show that tourists' attitude toward local food were positively and significantly influenced by their epistemic, emotional, functional, and interaction values. However, prestige value had no significant effect on tourists' attitude or behavioral intention. Interaction value had a significant influence on foreign tourists' attitude toward food, but not on their willingness to recommend and spread positive things about local culinary practices to others. The findings imply that food business owners and food destination marketers need to strategically develop and design effective promotions to promote local food as a destination marketing tool and attract more international tourists to a destination.
Keywords: 650; Culinary; food consumption value; attitude toward local food; behavioral intention; indonesia